Building Sustainable Peace through Business Linkages among Micro-Entrepreneurs: Case Studies from the North and East of Sri Lanka - Yoosuf, Amina; Premaratne, S.P. (University of Colombo, 2015)
While literature on peacebuilding and recbnciliation emphasizes the need for stakeholders at all levels of society to be engaged in peace and reconciliation for peace to be sustainable, no study can be found on how the development of business linkages contributes to reconciliation for peace in post-conflict areas. This paper examines the nature of business linkages and the role played by business linkages among microentrepreneurs and their contribution to reconciliation. It also examines the development of business and social linkages among entrepreneurs from the North and the East of Sri Lanka and their first excursions into the rest of the country. The case study method is used to study two projects, one implemented in the Ampara district, and the other currently being implemented in the five districts of the Northern Province. Findings from the East have validated the hypothesis that through a group approach, entrepreneurs learn and profit from the experiences of their counterparts.
Keywords: Peacebuilding and reconciliation, Post-conflict areas, Entrepreneur ship, Social and business networks.